Glucocorticoids acutely increase cell surface Na(+)/H(+) exchanger-3 (NHE3) by activation of NHE3 exocytosis - Bobulescu, I. Alexandru (2005)
Glucocorticoids have important effects on renal function, including the modulation of renal acidification by the major proximal tubular Na(+)/H(+) exchanger, NHE3. While the chronic effect of glucocorticoids is considered to be primarily at the transcriptional level, with increases in NHE3 mRNA and protein expression driving increased transport activity, the mechanisms by which glucocorticoids activate NHE3 in an acute setting have not been investigated. Previous studies have shown that a glucocorticoid-stimulated increase in NHE3 activity can occur before any detectable change in NHE3 mRNA. The present study examines the acute effects of glucocorticoids on NHE3 using opossum kidney (OKP) cells as a cell model. In OKP cells, total NHE3 protein abundance was not changed by 3 h of treatment with dexamethasone (10(−6) M). However, the biotin-accessible fraction representing NHE3 at the apical membrane as well as Na(+)/H(+) exchange activity measured fluorimetrically using the pH-sensitive dye BCECF-AM were significantly increased. These effects were not prevented by the protein synthesis inhibitor cycloheximide. NHE3 insertion (biotinylatable NHE3 after sulfo-NHS-acetate blockade) was stimulated by dexamethasone incubation, with or without cycloheximide. The rate of NHE3 endocytic retrieval, assessed either by the avidin protection assay (early endocytosis) or by the sodium 2-mercaptoethane sulfonate (MesNa) cleavage assay (early and late endocytosis), was not affected by dexamethasone. These findings suggest that trafficking plays a key role in the acute stimulation of NHE3 by glucocorticoids, with exocytosis being the major contributor to the glucocorticoid-induced rapid increase in cell surface NHE3 protein abundance and Na(+)/H(+) exchange activity.